An oceanographic survey for oil spill monitoring and model forecasting validation using remote sensing and in situ data in the Mediterranean Sea. (November 2016) - Pisano, A.; De Dominicis, M.; Biamino, W.; Bignami, F.; Gherardi, S.; Colao, F.; Coppini, G.; Marullo, S.; Sprovieri, M.; Trivero, P.; Zambianchi, E.; Santoleri, R.
Abstract: A research cruise was organized on board the Italian National Research Council (CNR) R/V Urania to test the oil spill monitoring system developed during the PRogetto pilota Inquinamento Marino da Idrocarburi project (PRIMI, pilot project for marine oil pollution). For the first time, this system integrated in a modular way satellite oil spill detection (Observation Module) and oil spill displacement forecasting (Forecast Module) after detection. The Observation Module was based on both Synthetic Aperture RADAR (SAR) and optical satellite detection, namely SAR and Optical Modules, while the Forecast Module on Lagrangian numerical circulation models. The cruise (Aug. 6–Sep. 7, 2009) took place in the Mediterranean Sea, around Sicily, an area affected by heavy oil tanker traffic with frequent occurrence of oil spills resulting from illegal tank washing. The cruise plan was organized in order to have the ship within the SAR image frames selected for the cruise, at acquisition time. In this way, the ship could rapidly reach oil slicks detected in the images by the SAR Module, and/or eventually by the Optical Module, in order to carry out visual and instrumental inspection of the slicks. During the cruise, several oil spills were detected by the two Observation Modules and verified in situ, with the essential aid of the Forecasting Module which provided the slick position by the time the ship reached the area after the alert given by the SAR and/or optical imagery. Results confirm the good capability of oil spill SAR detection and indicate that also optical sensors are able to detect oil spills, ranging from thin films to slicks containing heavily polluted water. Also, results confirm the useful potential of oil spill forecasting models, but, on the other hand, that further work combining satellite, model and in situ data is necessary to refine the PRIMI system.